AKTUALISASI NILAI SOSIAL KEMASYARAKATAN 'HANDEP HAPAKAT' DALAM UPACARA KEMATIAN PENGANUT HINDU KAHARINGAN - Budi Purnomo; Suryadi Penyang (Dharma Duta, 2018)
Hindu Kaharingan is a belief system adopted by people in the Central Kalimantan. Religious practice of Hindu Kaharingan has provided unique features and characteristics that distinguish it from other religions. The death ceremony is one religious practice of Hindu Kaharingan which consists of long ceremonial stages, starting from the initial stage to the last stage and of course involves the role of various parties and related elements to run well and smoothly. The occurrence of social interaction among Hindu Kaharingan people often involves the attitude of'handep hapakat' as self-actualization in fostering the values of sincerity, loyalty, help, the spirit of unity, mutual cooperation, and devotion to God Almighty in order to implement religious teaching practices well, smooth and sacred